Some Results on Super Heronian Mean Number of Graphs - S. S. Sandhya; E. Ebin Raja Merly; G. D. Jemi (International Journal of Mathematics And its Applications, 2018)
We add to some fresh outcomes for Super Heronian Mean Number of graphs. It has been found that the graphs obtained by the collection of Super Heronian Mean Number of Ladder, Triangular snake, Double Triangular snake also admit Super Heronian Mean Number.